A case of ischemic stroke in the basal ganglia presenting with fecal and urinary incontinence as initial clinical manifestations - Houde Li; Jiaxin Dai (BMC Neurology)
Abstract Limb disorders and slurred speech are common clinical symptoms associated with acute ischemic stroke. Although urinary incontinence is a known symptom in many cases of acute ischemic stroke, the simultaneous impairment of both bowel and bladder function is relatively rare. The occurrence of fecal and urinary incontinence as the primary clinical manifestation in minor acute ischemic stroke is especially uncommon. In this study, we present the case of a 67-year-old male patient who experienced a minor acute ischemic stroke in the basal ganglia region, notably presenting with both fecal and urinary incontinence. We also review the relevant literature to explore the potential causes behind this unusual presentation.